Determination of phospholipids as biomarkers of brain tissue damage in acute lymphoblastic leukemia patients - Miketová, Petral|Moore, Ida M. (Ki)l|Pasvogel, Alicel|Khailová, Ludmilal|Schram, Karl H.l|Hutter, John J.l|Kaemingk, Kristine L. (Univerzita Pardubice, 2003)
The application of a high performance liquid chromatography method was described for determination of phospholipid levels in the cerebrospinal fluid of children suffering with acute lymphoblastic leukemia (ALL). The levels of two major membrane phospholipids (phosphatidycholine and sphingomyelin) were monitored during the course of therapy and compared among three different therapeutic protocols. The monitored levels were correlated with the results of cognitive testing and assessed as biomarkers of cellular damage associated with ALL treatment.
Keywords: fosfolipidy; stanovení; Vysokoúčinná kapalinová chromatografie; biologické materiály